Program Revitalisasi Eduwisata Lokalisasi Dolly pada Humas Pemerintah Kota Surabaya - Fitria Widiyani Roosinda; Noviar Renindia Rachman (Fakultas Ilmu Komunikasi UKWMS, 2021)
This research’s tittle of Revitalization Program Of The Dolly Localization Tour Public Relations Surabaya City Goverment. Surabaya City Goverment Public Relations closed the prostitution activity in Dolly localizations by used the revitalization program. The program was carried out by the Surabaya Goverment by officially closing Dolly’s localization on June 18, 2014 and maked the former localization a eduwisata village and empowering local residents. This have done to help their economy after each individual after they get moved to another job. And the establishment of the eduwisata village and several child-friendly public facilities. The purpose of this research is to find out what are the steps taken by the Surabaya City Goverment Public Relations in their success in conduction the revitalization program. This research uses a descriptive qualitative research approach,. researcher used the direct interview method to the Surabaya City Goverment Public Relations as the main resource. After that, the researcher concluded what was done by the Surabaya City Goverment, especially the public relations agencies, along with the result they obtained. Dont forget also the various obstacles that occur when the revitalization program takes place.